1995
DOI: 10.1007/bf01701478
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis colonisation and endocarditis in five intensive care patients as late sequelae of selective decontamination

Abstract: We observed 5 patients with E. faecalis endocarditis as a late and severe sequela of SDD during their ICU stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…This has been suggested by others (7,10,21,25) and by us (4,5). Two placebo-controlled SDD trials, using colistin and tobramycin for topical prophylaxis, reported increased rates of infection with gram-positive cocci in patients receiving SDD (7,10).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This has been suggested by others (7,10,21,25) and by us (4,5). Two placebo-controlled SDD trials, using colistin and tobramycin for topical prophylaxis, reported increased rates of infection with gram-positive cocci in patients receiving SDD (7,10).…”
Section: Discussionmentioning
confidence: 58%
“…In the study by Hammond et al, oropharyngeal colonization with methicillinresistant Staphylococcus aureus was observed more frequently in SDD-treated patients (10). In a recent report, SDD with amphotericin B, polymixin E, and norfloxacin was associated with five cases of endocarditis caused by E. faecalis (21). In contrast, others have failed to demonstrate a relationship between SDD and rectal carriage with enterococci (11).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Enterococcal infective endocarditis is nosocomial in up to 39 % of the cases (Anderson et al 2004). E. faecalis endocarditis is known to occur in patients after intensive care (Sijpkens et al 1995). The ability of E. faecalis to colonize vascular tissue is thought to be by adhesin-ligand interactions between its surface determinants and host proteins at the sites of endovascular injuries (Mohamed et al 2004;Nallapareddy and Murray 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Because SDD is not active against resistant Gram-positive bacteria, it may promote colonization with bacteria such as S. Aureus , and E. faecalis and it can lead to infections with these bacteria in critically ill patients [9092]. Patients' illness causes conversion of carriage of normal to abnormal flora.…”
Section: Discussionmentioning
confidence: 99%